FAKTOR-FAKTOR PENENTU STRUKTUR MODAL PADA PERUSAHAAN PROPERTY, REAL ESTATE, AND BUILDING CONSTRUCTION YANG TERDAFTAR DI BURSA EFEK INDONESIA - Magister Manajemen, Pascasarjana FEB UNTAN (Equator Journal of Management and Entrepreneurship (EJME), 2020)
This research aims to analyze how much influence the profitability, tangibility, growth opportunities, non-debt tax shields, free cash flow on capital structure with company size as a moderating variable. Data analysis model used in this research is descriptive statistical analysis and inference. The population in this research are property, real estate and building construction companies listed on the Indonesia Stock Exchange during the period of 2013-2017. The samples were selected by using purposive sampling of 45 companies which sample companies collected with the criteria of having financial reports in a row during the research period. The research results show that the variable of profitability, tangibility, free cash flow had a negative and significant effect on capital structure. While the growth opportunity variable has a positive and significant effect on capital structure. Non-debt tax shields have no effect on capital structure. In addition, company size as a moderating variable has a significant effect as moderation between the relationship of tangibility to capital structure and growth opportunities to capital structure, but does not moderate the relationship of profitability to capital structure, non-debt tax shields to capital structure and free cash flow to capital structure.